Clinical Factors Associated With Congenital Cytomegalovirus Infection: A Cohort Study of Pregnant Women and Newborns - Uchida, Akiko; Tanimura, Kenji; Morizane, Mayumi; Fujioka, Kazumichi; Morioka, Ichiro; Oohashi, Masanobu; Minematsu, Toshio; Yamada, Hideto (Clinical infectious diseases, 2020)
Abstract Background The aim of this prospective cohort study was to determine clinical factors associated with the occurrence of congenital cytomegalovirus infection (cCMV) in pregnant women. Methods Between March 2009 and November 2017, newborns born at a primary maternity hospital received polymerase chain reaction (PCR) analyses for CMV DNA in their urine with informed consent of the mothers at a low risk. Clinical data, including age, gravidity, parity, body mass index, occupation, maternal fever/flulike symptoms, pregnancy complications, gestational weeks at delivery, birth weight, and automated auditory brainstem response, were collected. Logistic regression analyses were performed to determine clinical factors associated with cCMV. Results cCMV was diagnosed by positive PCR results of neonatal urine in 9 of 4125 pregnancies. Univariate and multivariable analyses revealed that the presence of fever/flulike symptoms (odds ratio [OR], 17.9; 95% confidence interval [CI], 3.7–86.7; P < .001) and threatened miscarriage/premature labor in the second trimester (OR, 6.0; 95% CI, 1.6–22.8; P < .01) were independent clinical factors associated with cCMV. Maternal fever/flulike symptoms or threatened miscarriage/premature labor in the second trimester had 100% sensitivity, 53.2% specificity, and a maximum Youden index of .85. Conclusions This cohort study for the first time demonstrated that these clinical factors of pregnant women and newborns were associated with the occurrence of cCMV. This is useful information for targeted screening to assess risks of cCMV in low-risk mothers, irrespective of primary or nonprimary CMV infection. The presence of maternal fever/flulike symptoms and threatened miscarriage/threatened premature labor in the second trimester were clinical factors associated with the occurrence of congenital CMV infection of newborns.